(untitled) (Journal of Computational Mathematics, 2018)
In this paper, some discrete-time finite element methods for nonlinear hyperbolic equations are derived and their theoretical analysis is given. The stability and the convergence of the finite element method for linear and semi-linear hyperbolic equations have already been discussed.